Manganese dioxides with different exposed crystal plane supported on g-C3N4 for photocatalytic H2 evolution from water splitting. (15th October 2022) - Liu, Xuecheng; Yan, Linjie; Hu, Xiting; Feng, Hongli; Guo, Bingke; Ha, Xia; Xu, Hui; Wang, Ruiqi; Tan, Xuemei; Huang, Hongyu
Abstract: A series of MnO2 /g-C3 N4 composites with different exposed crystal plane were successfully prepared by different synthesized method. UV–Vis, PL, ESR and electrochemical results suggest that the visible-light absorbance, photoexcited electron-separation efficiency and oxygen defects are greatly dependent on the exposed crystal-faceted MnO2 supported on g-C3 N4 . The experimental results display that the exposed crystal plane of MnO2 have great influences on the photocatalytic hydrogen evolution performance, and the m-MnOCN composite with exposed (111) crystal plane exhibits superior photocatalytic performance for the release of H2 under visible light irradiation, followed by the order of b-MnOCN [002]> p-MnOCN [110]. Moreover, Mechanism studies have shown that the possible mechanism of photocatalytic hydrogen evolution reaction is Z-scheme mechanism. Highlights: Photocatalytic hydrogen evolution performance of MnO2 /g-C3 N4 is enhanced with different exposed crystal plane. The m-MnOCN composite with exposed (111) crystal plane exhibits superior photocatalytic performance. The Z scheme mechanism is proposed for the photocatalytic hydrogen evolution mechanism of MnO2 /g-C3 N4 composite.